2020
DOI: 10.1158/0008-5472.can-19-2568
|View full text |Cite
|
Sign up to set email alerts
|

Futibatinib Is a Novel Irreversible FGFR 1–4 Inhibitor That Shows Selective Antitumor Activity against FGFR-Deregulated Tumors

Abstract: Fibroblast growth factor receptor (FGFR) signaling is deregulated in many human cancers and FGFR is considered a valid target in FGFR-deregulated tumors. Here we examine the preclinical profile of futibatinib (TAS-120; 1-[(3S)-[4-amino-3-[(3,5-dimethoxyphenyl)ethynyl]-1Hpyrazolo[3,4-d] pyrimidin-1-yl]-1-pyrrolidinyl]-2-propen-1-one), a structurally novel, irreversible FGFR1-4 inhibitor. Among a panel of 296 human kinases, futibatinib selectively inhibited FGFR1-4 with half-maximal inhibitory concentration (IC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 50 publications
2
118
0
1
Order By: Relevance
“…Moreover, a novel covalent, irreversible FGFR inhibitor (TAS-120, Frutibatinib) is in clinical development [103]. This TKI overcomes resistance to ATP-competitive FGFR inhibitors [104].…”
Section: Fgfr2 Alterationsmentioning
confidence: 99%
“…Moreover, a novel covalent, irreversible FGFR inhibitor (TAS-120, Frutibatinib) is in clinical development [103]. This TKI overcomes resistance to ATP-competitive FGFR inhibitors [104].…”
Section: Fgfr2 Alterationsmentioning
confidence: 99%
“…The highly selective, irreversible FGFR1, FGFR2, FGFR3, and FGFR4 inhibitor futibatinib (TAS-120) was firstly evaluated in a phase I study, the FOENIX-101, where 86 patients with previously treated advanced malignancies received this molecule (NCT02052778) [ 42 , 83 , 84 , 85 ]. According to the results of this dose-escalation trial, 20 mg once daily was established as the recommended phase II dose, with PR reported in five patients and SD in 41 subjects [ 83 , 84 , 85 ]. Based on these preliminary findings, futibatinib was assessed in the phase II FOENIX-CCA2 trial evaluating the FGFR inhibitor in CCA patients who had experienced disease progression on standard treatments or were not eligible for standard therapy [ 42 , 86 ].…”
Section: Fgfr-targeted Therapies In Cca: Non-selective and Selective Inhibitorsmentioning
confidence: 99%
“…Futibatinib is an oral FGFR1-4 highly selective irreversible inhibitor administered orally at a dose of 20 mg once daily in 21-day cycles [44]. A recently presented interim analysis of the FOENIX-CCA2…”
Section: Futibatinibmentioning
confidence: 99%